Radicalizing rawls global justice and the foundations of international law - Chartier, Gary.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book is a critical examination of John Rawls's account of the normative grounds of international law, arguing that Rawls unjustifiably treats groups - rather than particular persons - as foundational to his model of international justice.
Keywords: Science; Science; Science, general